2020
DOI: 10.21856/j-pep.2020.3.14
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Дослідження виконано в рамках НДР «Корекція розладів репродуктивної функції при експериментальній моделі простатиту у щурів за допомогою наночастинок на основі оксидів рідкісноземельних елементів» Досліджені зразки наночастинок було синтезовано в Інституті сцинтиляційних матеріалів НАН України на підставі Договору про наукову співпрацю між ДУ «Інститут проблем ендокринної патології ім. В. Я. Данилевського НАМН України» (м. Харків) та Інститутом сцинтиляційних матеріалів НАН України (м. Харків) від 07.02.2018 р… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Analyzing previous studies and data from literature sources found a positive effect of nanobiomaterials on the body of males with gonadopathy (Koshevoi et al, 2016;Koshvoy et al, 2021;Karpenko et al, 2020;Yaremchuk et al, 2017). The results of studies on their use to improve reproducibility, indicate a significant clinical and biochemical effect of the complex drug 'Karafand+OV,Zn".…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Analyzing previous studies and data from literature sources found a positive effect of nanobiomaterials on the body of males with gonadopathy (Koshevoi et al, 2016;Koshvoy et al, 2021;Karpenko et al, 2020;Yaremchuk et al, 2017). The results of studies on their use to improve reproducibility, indicate a significant clinical and biochemical effect of the complex drug 'Karafand+OV,Zn".…”
Section: Resultsmentioning
confidence: 95%
“…For the treatment of animals with gonadal pathology, drugs based on nanobiomaterials have been proposed, which have pronounced antioxidant and androgenstimulating effects and increase the body's overall resistance (Karpenko et al, 2020;Koshevoy et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The high antioxidant activity of these NPs makes it possible to use DOI: https://dx.doi.org/10.54203/scil.2022.wvj37 them as geroprotectors (Nikitchenko et al, 2021a). The positive effect of gadolinium orthovanadate NPs on the reproductive function of male rats with reproductopathy and experimental prostatitis has been proven (Belkina et al, 2017;Karpenko et al, 2020). Therefore, the aim of the study was to investigate the effect of gadolinium orthovanadate NPs on the dynamics of sperm quality, sex hormones, and oxidative/antioxidant balance in male rabbits affected by OS.…”
Section: Introductionmentioning
confidence: 99%